An analytical study of the reality of classroom management for postgraduate student in sports management from the students' point of view - Al-Hamdani, Fouad Abdul Mahdi Mahmoud (Universitas Tanjungpura, 2025)
Background. The success of the educational process requires cooperation between the main pillars of this variable. Otherwise, many major problems will arise and are likely to worsen, leading to the failure of the entire educational process. Objectives. The purpose of this study is to analyze and identify the strengths and weaknesses in the classroom management process of sports management courses for graduate students. Methods. The study employs a qualitative research design, where the researcher analyzes classroom management practices for postgraduate students in sports management at the Faculty of Physical Education and Sports Sciences. The research involves an investigation of the academic performance of students in universities in Maysan and Dhi Qar, identifying common issues related to the low scientific level of students in the subject. The researcher also explores various teaching methods, student engagement strategies, and classroom management techniques. In addition, data is collected through a review of student academic results, interviews, and classroom observations. Results. The findings of the study indicate that several factors contribute to the low academic performance of postgraduate students in sports management, despite their prior qualifications. These factors include ineffective classroom management practices, a lack of engaging teaching methods, and the failure to connect theoretical knowledge with practical examples. Additionally, students' inability to retain and apply course material in real-life scenarios was identified as a major weakness. However, some strengths in the classroom management process were noted, such as the researcher’s efforts to present the material in an accessible manner and integrate examples from daily life. The study revealed that with improvements in teaching approaches and classroom management, students' academic performance could be significantly enhanced. Conclusion. This study underscores the need for improved classroom management strategies and teaching methods to address the weaknesses observed in the postgraduate students' academic performance. It recommends the adoption of more interactive and practical teaching techniques, which would help students better connect theoretical knowledge with real-world applications. Furthermore, the study highlights the importance of fostering an engaging learning environment that encourages student participation and enhances knowledge retention.